Pemberdayaan Perempuan Ruhama Simpang Kapuak Kecamatan Mungka melalui Digitalisasi dan Manajemen Keuangan dalam Penguatan Usaha Teh Gambir Lokal - Amri Syahardi; Rivo Yulse Viza; Heri Faisal Harahap; Muhammad Hardian Syaputra; Eko Wahyu Apriansyah (Yayasan Literasi Sains Indonesia, 2025)
Micro, small, and medium enterprises (MSMEs), particularly those managed by women in rural areas, play a crucial role in supporting family and local economies. However, this potential is often hampered by limited access to technology and understanding of modern business management. The Ruhama women's group in Simpang Kapuak Village, Mungka District, faces similar challenges in its local gambir tea production business. This community service program aims to address these obstacles through strategic interventions in digital marketing and financial management. Implementation methods include outreach, theoretical training, and intensive practical mentoring. The activity stages are systematically designed, starting with needs analysis and program implementation, and ending with impact evaluation, measured by increasing empowerment levels. The results demonstrate significant improvements in digital literacy and financial management skills among participants. 85% of participants are able to create promotional content for products on social media, and 92% understand the basic concepts of simple financial record keeping. Close collaboration with the village government also strengthens program synergy, aligning with the regional development vision. The program has not only succeeded in improving technical capacity but also fostering an entrepreneurial spirit and independence, which are essential foundations for the economic sustainability of local communities.